2014
DOI: 10.1371/journal.pone.0090898
|View full text |Cite
|
Sign up to set email alerts
|

Reduced-Gliadin Wheat Bread: An Alternative to the Gluten-Free Diet for Consumers Suffering Gluten-Related Pathologies

Abstract: Wheat flour cannot be tolerated by those who suffer allergies to gluten. Human pathologies associated with grain proteins have increased worldwide in recent years, and the only effective treatment available is a lifelong gluten-free diet, which is complicated to follow and detrimental to gut health. This manuscript describes the development of wheat bread potentially suitable for celiac patients and other gluten-intolerant individuals. We have made bread using wheat flour with very low content of the specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 67 publications
2
77
0
Order By: Relevance
“…Bread prepared with low-gliadin flour presented higher lysine content and final bread quality, similar to normal bread. Whereas bread volume showed a reduction between about 20% and 30% compared to control (Gil-Humanes et al, 2014). Details about these investigations can be found in the review of Rosell et al (2014).…”
Section: Genetically Modified Wheat Breedingmentioning
confidence: 96%
“…Bread prepared with low-gliadin flour presented higher lysine content and final bread quality, similar to normal bread. Whereas bread volume showed a reduction between about 20% and 30% compared to control (Gil-Humanes et al, 2014). Details about these investigations can be found in the review of Rosell et al (2014).…”
Section: Genetically Modified Wheat Breedingmentioning
confidence: 96%
“…Gil-Humanes et al described the development of wheat bread from flour with very low content of the specific gluten proteins (near gliadin-free) potentially suitable for celiac patients and other gluten-intolerant individuals (44). These breads showed baking and sensory properties, and overall acceptance similar to those of normal flour.…”
Section: Food Engineeringmentioning
confidence: 99%
“…() reported that major reductions in the α‐gliadins do not cause major differences in flour functionality with only a slightly detrimental effect in microbaking tests. Alteration of protein structure has also been achieved through genetic manipulation of specific gluten proteins to reduce the gluten immunoresponse (Gil‐Humanes et al ., ) by reducing the gliadin content by up to 97%. The transgenesis technological properties of doughs prepared from the low‐gliadin lines might be applied to other nontoxic cereals, as raw material to produce GF products (Gil‐Humanes et al ., ).…”
Section: Other Approaches To Improve Gf Baked and Pasta Qualitymentioning
confidence: 99%